2018
DOI: 10.1089/tmj.2017.0123
|View full text |Cite
|
Sign up to set email alerts
|

Use of Short Message Service and Smartphone Applications in the Management of Surgical Patients: A Systematic Review

Abstract: Mobile interventions provide a sophisticated yet simple tool to improve perioperative healthcare. Future considerations to address include usage fatigue and Health Insurance Portability and Accountability Act compliance concerns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 34 publications
0
50
0
1
Order By: Relevance
“…Short message service (SMS) text messaging, smart-phone applications, automated calls and wearable devices have become some of the most widely used modalities (21). SMS-based communications have been widely adopted over the years, and are used twice as frequently compared to application-based interventions (32). Generally, any cellphone or computer can send and receive SMS texts, providing a very basic and easy-to-use modality for patient communication.…”
Section: Telemedicine Modalitiesmentioning
confidence: 99%
“…Short message service (SMS) text messaging, smart-phone applications, automated calls and wearable devices have become some of the most widely used modalities (21). SMS-based communications have been widely adopted over the years, and are used twice as frequently compared to application-based interventions (32). Generally, any cellphone or computer can send and receive SMS texts, providing a very basic and easy-to-use modality for patient communication.…”
Section: Telemedicine Modalitiesmentioning
confidence: 99%
“…Patients are also more likely to adhere to post-operative and discharge instructions when using mHealth apps (10). Those who engage with mHealth apps show greater patient satisfaction, better medication adherence, improved clinic attendance, lower readmission, and emergency department visits post-operatively (11). One study found that in the absence of an mHealth application, up to 55% of patients would have returned to the hospital for assessment of their wounds (12).…”
Section: Review Enhanced Information Deliverymentioning
confidence: 99%
“…Multiple digital platforms exist that utilize email or portal sites to enhance patient-provider communication. 16 Nevertheless, these arrangements may fall short because they require smartphone or computer access, which are unavailable to many patients, particularly those of lower socioeconomic status. 16 Use of an SMS-or phone call-based intervention, on the other hand, allows providers to engage a larger portion of patients due to the near-ubiquitous capability of all phones to answer basic text messages or phone calls.…”
Section: Discussionmentioning
confidence: 99%
“…16 Nevertheless, these arrangements may fall short because they require smartphone or computer access, which are unavailable to many patients, particularly those of lower socioeconomic status. 16 Use of an SMS-or phone call-based intervention, on the other hand, allows providers to engage a larger portion of patients due to the near-ubiquitous capability of all phones to answer basic text messages or phone calls. 17 These results suggest that EpxDecol and EpxWound effectively engage a broad range of patients in the perioperative process, as demonstrated through high response proportions that declined minimally over the length of each intervention.…”
Section: Discussionmentioning
confidence: 99%